Atypical free‐floating iridociliary pigmented epithelial cysts and secondary glaucoma in a caiman (Caiman latirostris). (16th February 2021) - Oriá, Arianne Pontes; Estrela‐Lima, Alessandra; Teixeira, Leandro B. C.; Dubielzig, Richard R.; Ofri, Ron
Abstract: We describe a case of chronic ocular trauma that resulted in fixed and free‐floating, pigmented epithelial iridociliary cysts, inflammation, and secondary glaucoma in a caiman ( Caiman latirostris ). A 20‐ to 25‐year‐old male caiman was presented with phthisis bulbi in the right eye, and congested episcleral vessels, corneal leukoma, disorganized anterior chamber, multifocal anterior synechia, and elevated intraocular pressure in the left eye. Ocular ultrasound of the left eye revealed round structures dispersed in the anterior and posterior chambers and vitreous cavity. Bilateral enucleation was performed, and gross pathology of the left eye revealed multiple pigmented cysts attached to the iris and posterior corneal surface causing marked distortion of the anterior uvea, and free‐floating in the vitreous cavity. Histopathology demonstrated heavily pigmented cystic structures of iridociliary epithelium origin carpeting the anterior segment surfaces and causing obstruction of the iridocorneal angles, leading to secondary glaucoma. To the authors' knowledge, this is the first report of iridociliary cysts in wildlife species.